Evolution and sources of manufacturing productivity growth: evidence from a panel of European countries - Silvia Giannangeli; Ramón Gómez-Salvador (European Central Bank (ECB), 2008)
The study aims at describing productivity growth in the manufacturing sector for a selected panel of five European countries using firm-level data. The paper explores the empirical regularities of firm productivity distribution across countries. In particular, we assess the degree of persistence of firm relative productivity and consider its effect on aggregate productivity improvements. Moreover, the paper analyses the impact of the competitive forces on aggregate productivity growth by disentangling the role of firm learning and market selection. Finally, we estimate the relationship between labour productivity growth and firm-specific factors such as size, age and capital intensity across countries. The paper uses annual account data over the period 1993-2003 from Amadeus dataset (Bureau van Dijk) for a balanced panel of manufacturing firms. In line with previous evidence, our analysis shows that firm relative productivity levels are both highly heterogeneous across firms and very persistent over time in all the countries in the sample. With reference to aggregate productivity growth, we find that both labour productivity and total factor productivity changes are mostly driven by firm learning, i.e. within-firm productivity improvements, in most European countries. Conversely, the reallocation of resources spurred by the competitive selection process is found to play a minor role in fostering aggregate productivity growth. Finally, in line with macroeconomic trends, gains in productivity seem to be associated with capital deepening, but also with employment losses.
Keywords: D24; L11; L60; 330; cross-country comparison; microdata; productivity growth; Industrie; Produktivität; Mikrodaten; Lernende Organisation; Marktaustritt; Arbeitsproduktivität; Belgien; Deutschland; Frankreich; Italien; Spanien